2015
DOI: 10.1016/j.juro.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Can Bladder Wall Thickness Predict Videourodynamic Findings in Children with Spina Bifida?

Abstract: Even if bladder wall thickness is measured at specifically defined bladder volumes, it cannot predict videourodynamic findings other than bladder trabeculation in children with spina bifida.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Kim et al 11 in their study on the role of BWT in predicting urodynamic findings, opined that there were no significant differences in BWT measured at each percent maximum cystometric capacity between patients with favorable or unfavorable video urodynamic findings. This could imply that BWT alone cannot be relied upon as a marker for the assessment of NB.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 11 in their study on the role of BWT in predicting urodynamic findings, opined that there were no significant differences in BWT measured at each percent maximum cystometric capacity between patients with favorable or unfavorable video urodynamic findings. This could imply that BWT alone cannot be relied upon as a marker for the assessment of NB.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, low compliance is a critical factor widely recognized as dangerous for the upper tracts and the term is freely used in literature and textbooks. [ 22 ] Contemporary studies have defined “low compliance” variously as <10 ml/cmH 2 O,[ 26 ]< 12.5 ml/cmH 2 O,[ 20 27 ] or <20 ml/cmH 2 O. [ 28 ] Others have stated the actual values noted without defining “low compliance.”[ 29 ] We chose to provide both the actual data as well as a defined numerical value for “low compliance.” A bimodal age distribution has been described with most children identified in infancy and the remainder by age five.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to correlate with ultrasonography findings with function have been unsuccessful, but did establish and association between bladder wall thickness and the presence of trabeculations when the bladder is at greater than 50% of filling capacity. 17…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to correlate with ultrasonography findings with function have been unsuccessful, but did establish and association between bladder wall thickness and the presence of trabeculations when the bladder is at greater than 50% of filling capacity. 17 Although the pathogenesis is unclear, response to treatment may depend on the presence of SBO. One study of children with nocturnal enuresis showed that none of the children with SBO had a response to desmopressin, defined as 90% or better improvement in the frequency of nocturnal bedwetting compared with the children without SBO.…”
Section: Discussionmentioning
confidence: 99%